11C-Methionine Uptake in the Lactating Human Breast. (January 2022) - Michler, Enrico; Hilliger, Stephan; Kopka, Klaus; Kotzerke, Jörg
Abstract : Abstract: A 33-year-old nursing mother who underwent resection of a glioblastoma of the right hemisphere was referred for a 11 C-methionine PET/MR scan to exclude cancer recurrence. In whole-body PET imaging, a slight radiotracer uptake could be observed in the mammary glands, reflecting lactation status. In this case report, we initially describe 11 C-methionine uptake in the human breast and discuss any consequences arising from this special situation.